2017
DOI: 10.1080/03043797.2017.1415299
|View full text |Cite
|
Sign up to set email alerts
|

Research-based education as a model to change the teaching and learning environment in STEM disciplines

Abstract: Research-based education as a model to change the teaching and learning environment in STEM disciplines This paper discusses the benefits and threats of promoting and reinforcing a research-based education environment to STEM undergraduate students. The paper explores the rationale for research-based education as a pedagogical driven approach, where undergraduate students learn through enquiry and discovery. Research evidence of a STEM case-study conducted in an English university is then presented, which shed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 40 publications
0
41
0
4
Order By: Relevance
“…In this study, the effects of STEM seminars on math literacy self-efficacy, mathematical thinking skills and technology level of use are investigated. STEM education has the objective to equip students with the knowledge, skills, attitudes and competencies that will enable them to cope with the uncertainty of the knowledge society (Huet, 2017). As a result of the study, it was found that STEM seminars changed the mathematics literacy selfefficacy of the teachers positively.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, the effects of STEM seminars on math literacy self-efficacy, mathematical thinking skills and technology level of use are investigated. STEM education has the objective to equip students with the knowledge, skills, attitudes and competencies that will enable them to cope with the uncertainty of the knowledge society (Huet, 2017). As a result of the study, it was found that STEM seminars changed the mathematics literacy selfefficacy of the teachers positively.…”
Section: Discussionmentioning
confidence: 90%
“…Así, se favorece el trabajo de grupos con diferentes estilos de aprendizaje, niveles de habilidades y antecedentes culturales. Los proyectos pueden incluir el diseño y desarrollo de un producto, servicio, marca, proceso, función u operación que puede ser visto o utilizado por otros, pero todos ellos de aplicación a escala real (Huet, 2018).…”
Section: Contextounclassified
“…Instructors use ECP for in-class demonstrations, for cooperative group experiments, and for homework assignments. It has been noted that experiential learning connects contents to real-world applications and such learning experiences have been instrumental in improving student performance and achievement especially among minority students in both face-to-face and online settings [12][13][14][15][16][17][18][19][20][21][22][23]. The paper will highlight the criteria used for selection of initial experiments to adapt, the modifications made, and resulting changes in the course delivery.…”
Section: Research Approachmentioning
confidence: 99%
“…The mobile boards have also been utilized in other disciplines such as mechanical engineering using two experiments developed and tested in a class. [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation